2015
DOI: 10.1111/jvp.12243
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and cardiovascular effects following a single oral administration of a nonaqueous pimobendan solution in healthy dogs

Abstract: Pimobendan is an inodilator used in the treatment of canine congestive heart failure (CHF). The aim of this study was to investigate the pharmacokinetics and cardiovascular effects of a nonaqueous oral solution of pimobendan using a single-dose, operator-blinded, parallel-dose study design. Eight healthy dogs were divided into two treatment groups consisting of water (negative control) and pimobendan solution. Plasma samples and noninvasive measures of cardiovascular function were obtained over a 24-h period f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
35
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(46 citation statements)
references
References 22 publications
10
35
0
3
Order By: Relevance
“…However, the therapeutic efficacy of the plasma concentrations reported in our study is difficult to interpret, partly because the plasma concentrations associated with the presumed efficacy of PIM and OMDP are not clearly defined in dogs. The authors noticed a disparity among the pharmacokinetic profiles of pimobendan reported by others (1,6,21). The key pharmacokinetic parameters of PIM and ODMP from different studies are summarized in Table 2.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…However, the therapeutic efficacy of the plasma concentrations reported in our study is difficult to interpret, partly because the plasma concentrations associated with the presumed efficacy of PIM and OMDP are not clearly defined in dogs. The authors noticed a disparity among the pharmacokinetic profiles of pimobendan reported by others (1,6,21). The key pharmacokinetic parameters of PIM and ODMP from different studies are summarized in Table 2.…”
Section: Discussionmentioning
confidence: 91%
“…While the oral bioavailability of the commercial tablet is 70% (1,2,6), oral administration is not a viable route in an emergency situation. Many dogs presenting with advanced stage of CHF are in severe respiratory distress on presentation.…”
Section: Introductionmentioning
confidence: 99%
“…O pimobendan é um composto orgânico, derivado de benzimidazolepiridazinona, classificado como fármaco inodilatador, por apresentar características inotrópicas e vasodilatadoras (EPOCH STUDY GROUP, 2002;POLLESELLO et al, 2016;YATA et al;).…”
Section: Históricounclassified
“…O pimobendan é um fármaco inodilatador, derivado de benzimidazolepiridazinona, que apresenta duplo mecanismo de ação, aumentando a sensibilização do cálcio intracelular, proporcionando aumento na contratilidade miocárdica e efeito vasodilatador por meio da inibição da fosfodiesterase 3 (PDE3) (YATA et al, 2016;GORDON et al, 2017).…”
Section: Mecanismo De Açãounclassified
See 1 more Smart Citation